Characteristics of Calorific Value and Moisture Content of Briquettes with Variations in Sugarcane Bagasse and HDPE Plastic Waste Composition : Karakteristik Nilai Kalor Dan Kadar Air Pada Briket Dengan Variasi Komposisi Ampas Tebu Dan Plastik HDPE - Siregar, Christavany Shinta Dewi; Febri Juita, Anggraini; Bambang , Irawan (Fakultas Teknik Universitas Hamzanwadi, 2025)
This study aims to analyze the effect of varying compositions of sugarcane bagasse and HDPE plastic waste on the calorific value and moisture content of briquettes as an alternative fuel. The research employed pyrolysis of sugarcane bagasse and melting of HDPE plastic, followed by the production of briquettes with different bagasse and HDPE ratios. Moisture content was tested using the oven method, while calorific value was measured with a bomb calorimeter according to applicable standards. The results showed that briquettes composed of 50% bagasse and 50% HDPE had the highest calorific value of 8172 cal/g and the lowest moisture content of 1.57%, meeting the quality standards for wood charcoal briquettes. The addition of HDPE plastic significantly contributed to increasing the energy value and reducing the moisture content of the briquettes. The study concludes that sugarcane bagasse waste and HDPE plastic can be optimally utilized as environmentally friendly and economical alternative energy sources